Dietary Conjugated Linoleic Acid Modulates the Hepatic Circadian Clock Program via PPARα/REV-ERBα-Mediated Chromatin Modification in Mice - Liu, Hao-Yu; Gu, Haotian; Li, Yanwei; Hu, Ping; Yang, Yatian; Li, Kaiqi; Li, Hao; Zhang, Kexin; Zhou, Bo; Wu, Huaxing; Bao, Wenbin; Cai, Demin (Frontiers in Nutrition, 2021)
Scope: Disruptions of circadian rhythm cause metabolic disorders and are closely related to dietary factors. Here we investigated the interplays between the dietary conjugated linoleic acid (CLA)-induced hepatic steatosis and the circadian clock regulation, in association with lipid homeostasis. Methods and results: Exposure of mice to 1.5% dietary CLA for 28 days caused insulin resistance, enlarged livers, hepatic steatosis, and increased triglyceride levels. Transcriptional profiling showed that hepatic circadian clock genes were significantly down-regulated with increased expression of the negative transcription factor REV-ERBα. We uncovered that the nuclear receptor (NR) PPARα, as a major target of dietary CLA, drives REV-ERBα expression via its binding to key genes of the circadian clock, including Cry1 and Clock, and the recruitment of histone marks and cofactors. PPARα or REV-ERBα inhibition blocked the physical connection of this NR pair, reduced the co-binding of PPARα and REV-ERBα to the genomic DNA response element, and abolished histone modifications in the CLA-hepatocytes. In addition, we demonstrated that CLA promotes PPARα driving REV-ERBα transcriptional activity by directly binding to the PPARE at the Nr1d1 gene. Conclusions: Our results add a layer to the peripheral clock feedback loop involving the PPARα-REV-ERBα and provide guidance for the circadian physiology of nutrients optimization.